Sustainable urban transport development strategy using network analysis (Case study: the structure of management in urban transport of Tabriz metropolis) - Zohreh Fanni; Tohid Ahmadi; Mohammadtagi Razavian (نشریه جغرافیا و برنامه‌ریزی, 2017)
Urban transportation is one of the most important issues in Iran metropolises, and despite the importance of this system in the metropolises of Iran, a strategic plan to guide the development of this system, are rare. Tabriz city as one of the country metropolis is no exception about problems caused by inefficient transportation system. And transportation in this city also needs a comprehensive and strategic plan. In terms of methodology, this research is descriptive - analytical and data collection done by library and field studies (interviews and questionnaires). In this process, validity of questionnaires is based on expert opinion and reliability was approved by using Cronbach's alpha. Then, using SWOT strengths and weaknesses and the opportunities and threats are analyzed, and the strategies that are Delphi and techniques outcome, have been prioritized using the ANP technique. The results of this research process indicate that the strategies in this planning are aggressive strategies based on the reinforcing the strengths and using the opportunities. Therefore, the strategies on aggressive approach using ANP model analyzed and their ultimate priority with the weight of each strategy has been set. The final result of ANP analysis shows that the highest score (0.395)is for the strategy SO1; (Taking advantage of the experience of the pilot projects that implemented in Tabriz and other metropolises in Iran, in the field of intelligent transportation systems in order to promote and develop intelligent transportation) and implementation of this strategy is the first priority.